Aging Effect on Electrical Conductivity of Pure and Al-Doped YBa2Cu3O7−δ Single Crystals with a Given Topology of Planar Defects - Ruslan V. Vovk; Nikolaj R. Vovk; Oleksandr V. Dobrovolskiy (Advances in Condensed Matter Physics)
The conducting properties in the basal ab plane of pure and Al-doped YBa2Cu3O7-δ single crystals before and after long-time exposure in air atmosphere are investigated. It is shown that prolonged aging leads to an increase of the density of effective scattering centers for the normal carriers. The aluminum doping has been revealed to partially slowdown the degradation of the conducting properties in process of aging. The excess conductivity, Δσ(T), has been found to obey exponential dependence in the broad temperature range Tc<T<T*. In the pseudogap regime, the mean-field transition temperature T* and the 3D-2D crossover point in the excess conductivity have been quantified. Near the critical temperature, Δσ(T) is described well within the Aslamazov-Larkin theoretical model. Herewith, both aluminum doping and prolonged aging have been found to essentially expand the temperature interval of implementation of the pseudogap state, thus narrowing the linear section in the dependence ρab(T).